Experience in Flap Reconstruction of Lower Limb Defects in a Tertiary Care Center of Nepal - Niraula, Himalaya; Rajbhandari, Bikesh; Devkota, Manish; Sharma, Samit; Rayamajhi, Sangam; Shrestha, Jayan M; Lohani, Ishwar (Journal of Institute of Medicine Nepal, 2021)
Introduction Lower limb defects are caused by trauma, chronic ulcers or oncological resection. Being a large and varied area of the body, lower limb reconstruction is challenging. This study analyzed clinical presentation of such defects, surgical management and outcomes in Nepalese context. Methods Single-center retrospective study of flap reconstruction of lower limb defects conducted in Tribhuvan University Teaching Hospital, Kathmandu over a two years period (April 2019-March 2021). Demographics, clinical presentation, comorbidities, treatment and complications were recorded and analyzed. Results A total of 53 flaps were performed on 47 patients with 50 defects (35 males and 12 females). Road traffic accidents (38.3%) and pressure ulcers (17.02%) were common causes. Ankle-foot was the most affected site (48%), followed by leg and thigh (18% each). Defect size ranged from 3 cm2 to 396 cm2. Surgery consisted of 46 pedicled and seven free flaps. Reverse sural artery flap was the commonest flap performed (30.2%). All free flaps were performed on defects larger than 100cm2. Overall complication rate was 30.2%, partial flap loss being the commonest (15.1%). Total flap loss occurred in one pedicled and one free flap. Eleven pressure ulcers were operated on, with 36.4% complication rate. Average hospital stay was 33.5±26.88 days. Conclusion Multiple surgeries, comorbidities and high complication rates with hospital stay of more than a month reflect the difficulties encountered in lower limb reconstruction. Despite these challenges, majority of our patients were discharged with stable wound coverage.